Proposta metodológica para o escopo da avaliação ambiental estratégica no contexto da fronteira agrícola brasileira - Berti, Maria José Ferreira (2014)
The Strategic Environmental Assessment (SEA) is an important tool for the integration of environmental dimension to elaborate Policies, Plans and Programs (PPPs). The SEA may contribute to the elaboration of Plans and Programs (PPs) in the agricultural sector, inserting values which are led to sustainability. In SEA, the scope is crucial for the proper fulfillment of the other steps, ensuring that the planning process from the start integrates environmental and social issues. The stage of the scoping establishes the focus and content of the SEA and the basic and relevant criteria for evaluation. In this context, the present study aims to present subsidies, through a proposal for guidelines for the development of SEAs scope step for plans and programs - PPs - the agricultural sector in the Brazilian Amazon, more specifically in the North and Northeast State of Mato Grosso, which are inserted in agricultural frontier areas in the Cerrado and in their transition to the Amazon biome. Due to the expansion of the agricultural sector in these regions, critical situations were identified in relation to environmental issues, such as accelerated deforestation, fires, loss of biodiversity and the decline in the level of quality of water and soil. These critical situations are related to actions induced by many PPs deployed in the region and SEA is a proper tool to evaluate the relationship between the development options of the agricultural sector in a sustainable manner in relation to natural resources and the effects resulting therefrom. The methodology used in the research was literature review, identifying support methodologies for the preparation of defining the scope of an SEA in the national and international context, collection of secondary data in government institutions, preparation of an environmental baseline and to hold two workshops with a multidisciplinary team of experts. Using driven approach baseline (baseline-led) a sequence of procedures was developed to provide subsidies to the definition of SEAs scope. It was sought to observe both the guiding principles of the European Directive 042/2001/CE and the a practical guide to the Strategic Environmental Assessment Directive of Office of the Deputy Prime Minister-ODPM of 2005, as well as to be based on the current good practices, checked in the bibliography review and in the analyzed case studies. The research main results are the context definition for SEA, the survey of the main PPs of the agricultural sector and the Interfering strategic actions, such as the energy and transportation, the environmental baseline construction, the identification of fundamental environmental themes and their indicators; and the elaboration of a matrix of identification and valuation of the environmental effects, which assist to identify relevant issues to define the SEA strategic objectives.